Operational Risk Identification and Mitigation Strategies in Rizky Strawberry Agrotourism - Ayutyas Sayekti; Hassa Nur Syamsa; Jarwadi Budi Hernowo (Jurnal Ragam Pengabdian, 2026)
Operational risk management is essential for ensuring the sustainability of newly established agrotourism enterprises operating under high uncertainty. This study examines operational risks in Rizky Strawberry Agrotourism, Sukabumi, and aims to identify, assess, and prioritize risks while formulating appropriate mitigation strategies. A case study approach was employed using in-depth interviews with five key internal stakeholders. The findings reveal ten operational risks categorized into human resource, system and regulatory, facilities and infrastructure, environmental, and external risks. Three risks were classified as very high and two as high, primarily related to employee competency gaps, safety management weaknesses, and infrastructure limitations. These risks indicate that early-stage agrotourism enterprises are highly vulnerable to internal managerial inefficiencies. The study confirms that operational sustainability in emerging agrotourism depends not only on resource potential but also on structured risk-based management. This research provides an applicable operational risk prioritization framework tailored to newly established agrotourism businesses. Unlike prior studies that examine tourism risk in general contexts, this research focuses specifically on operational risk structures in early-stage agrotourism enterprises and integrates risk measurement, prioritization, and mapping into a practical decision-support framework.